Non-alcoholic fatty liver disease and cognitive impairment - Elena V. Onuchina; Bairma B. Dambaeva; Anna G. Glazunova; Ayuna Kh. Mikhailova; Elena M. Vorobyova; Elena I. Soshina; Natalya V. Efremenko (Терапевтический архив, 2024)
Aim. To evaluate the efficacy of oral administration of the original ademetionine (Geptral) at a dose of 1500 mg/s in patients with NAFLD at the steatosis stage and cognitive impairment within the framework of a prospective observational open non-comparative study in real clinical practice against the background of achieved lifestyle modification.